(untitled) (Simbiótica. Revista Eletrônica, 2026)
The image of the social science professional and their training process has historically been centered on teaching at the higher and basic education levels, relegating professional practice outside academic and school settings to a secondary role. Recently, the process of integrating extension activities into the curriculum has opened opportunities for the inclusion of curricular activities aimed at developing skills that enable students to engage in dialogue with civil society, governments, and the market. In this context, a still modest but growing movement of interest in applied research is observed. This article aims to contribute to this debate by presenting an experiential account of the extension course “Practices of Applied Social Research” offered in the undergraduate Social Science program at the Federal University of Rio Grande do Sul since 2023. Through this account, we highlight seven challenges for incorporating applied social research into social science curricula and reflect on the potential of this experience for the training of social scientists.